Determinant Employee Performance Through Individual Characteristics, Quality of Work Life, and Work Facilities - Rizki, Via Lailatur; Muttaqien, Fauzan; Fitria, Novy; Irwanto , Jesi (Jurnal Ilmu Manajemen Advantage, 2024)
Optimal performance is often influenced complexity factors, including individual characteristics, quality of work life and work facilities which are one of the company's operational references in improving performance. Employee performance is the main focus of every company in order to achieve related goals. The case study in this research is at PT. Serbuk Jaya Abadi found in Lumajang. The purpose of study is to examine the effect of   individual   characteristics, quality   life   work   and    facilities   work   effect on     performance    employees. Population of this study 150 employess.   This   research   used the Slovin  method sampling  and distributing   questionnaires   to   60   samples   namely     employees   PT.    Serbuk Jaya Abadi     obtained   from   sampling   method. The   analysis   method in   this   research   uses   analysis   multiple   linear   regression   with   results, individual   characteristics   do not   has a   significant  effect on  performance,  quality  of work life has a  significant effect on  performance,  work facilities  has a  significant effect on performance.